1997
DOI: 10.1177/002215549704500704
|View full text |Cite
|
Sign up to set email alerts
|

A Covalent Fluorescent–Gold Immunoprobe: Simultaneous Detection of a Pre-mRNA Splicing Factor by Light and Electron Microscopy

Abstract: Immunoprobes that combine a fluorescent label with a 1.4-nm gold cluster compound have been prepared by covalent conjugation with polyclonal antibody Fab' fragments. These new immunoconjugates allow the collection of two complementary sets of data, from fluorescence and electron microscopy, from a single labeling experiment. We find that incorporation of one or more fluorescein moieties into the coordinated ligands of the 1.4-nm Nanogold gold cluster label yields a stable, dual-function immunolabel in which fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 26 publications
0
54
0
Order By: Relevance
“…This methodology has not been widely used because the colloidal gold tends to quench the fluorescence signal (e.g., Goodman et al 1991). FNG was developed as an alternative immunoprobe (Powell et al 1997). This fluorescent immunoprobe is distinct from the colloidal gold-fluorescent probes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This methodology has not been widely used because the colloidal gold tends to quench the fluorescence signal (e.g., Goodman et al 1991). FNG was developed as an alternative immunoprobe (Powell et al 1997). This fluorescent immunoprobe is distinct from the colloidal gold-fluorescent probes.…”
Section: Discussionmentioning
confidence: 99%
“…FNG has several advantageous properties as an immunoprobe for correlative microscopy: (a) the fluorescence signal does not appear to be reduced because of proximity to the gold cluster; (b) the fluorochrome and antibody do not readily dissociate from a 1.4-nm gold particles because they are covalently linked [dissociation of antibodies from colloidal gold immunoprobes has been reported (Kramarcy and Sealock 1991)]; and (c) FNG penetrates into cells as readily as conventional immunofluorescence probes (Robinson and Vandré 1997). Previous studies have shown FNG to be a valuable immunoprobe for correlative microscopy (Powell et al 1997;Robinson and Vandré 1997). Although these approaches for correlative microscopy have been helpful for morphological analysis, they did not fully explore the capabilities of the methodology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional tools for immunolabeling are fluorescent derivatives of NG known as FluoroNanogold (FNG) (Powell et al 1997). These bifunctional probes consist of a 1.4-nm gold cluster compound to which an antibody [IgG, F(ab Ј ) 2 , or Fab] is conjugated; fluorochromes are conjugated to the antibody.…”
Section: Applications Using Fluoronanogoldmentioning
confidence: 99%
“…Resonant energy transfer (RET) systems consisting of organic dye molecules and noble metal nanoparticles have recently gained considerable interest in biophotonics [1][2][3][4] as well as in materials science [5,6]. Closely related are donor-acceptor pairs of organic dye molecules forming Förster resonant energy transfer (FRET) systems.…”
mentioning
confidence: 99%